Jasmonates in plant growth and development and elicitation of secondary metabolites: An updated overview - Sohn, Soo-In; Pandian, Subramani; Rakkammal, Kasinathan; Largia, Muthiah Joe Virgin; Thamilarasan, Senthil Kumar; Balaji, Sekaran; Zoclanclounon, Yedomon Ange Bovys; Shilpha, Jayabalan; Ramesh, Manikandan (Frontiers in Plant Science, 2022)
Secondary metabolites are incontestably key specialized molecules with proven health-promoting effects on human beings. Naturally synthesized secondary metabolites are considered an important source of pharmaceuticals, food additives, cosmetics, flavours, etc., Therefore, enhancing the biosynthesis of these important specialised metabolites by maintaining natural authenticity is getting more attention. The application of exogenous jasmonates is well recognised for its ability to trigger plant growth and development. They have also been found to be an effective chemical booster for the synthesis of naturally occurring secondary metabolites. This review discusses the significance of jasmonates in the growth and development of plants and the successful outcomes of jasmonate-driven elicitation of secondary metabolites including flavonoids, anthraquinones, anthocyanin, xanthonoid, and more from various plant species. However, as the enhancement of these metabolites is essentially measured via in vitro cell culture, or foliar spray, production at a large scale is limited. Recent advancements in plant cell culture technology pave the way for large-scale manufacturing of plant-derived secondary metabolites. With the knowledge regarding the genetic background of the metabolite biosynthetic pathway, synthetic biology also appears to be a potential avenue for accelerating their production. The information presented here is essential for producing plant secondary metabolites on a large-scale using plant cell, tissue and organ cultures.